Use of a novel floxed mouse to characterise the cellular source of plasma coagulation FXIII-A. (26th February 2015) - Griffin, Kathryn; Simpson, Kingsley; Beckers, Cora; Brown, Jane; Vacher, Jean; Ouwehand, Wilhelm; Alexander, Warren; Pease, Richard; Grant, Peter
Abstract: Background: Coagulation factor XIII-A has a crucial role in thrombus stabilisation and tissue repair. Factor XIII-A deficiency causes a severe bleeding phenotype and impaired wound healing, but the cellular origin of Factor XIII-A is unknown. To identify the cells that maintain the plasma pool, we generated a mouse floxed in coding exon7 of the factor XIII-A gene ( F13A1 ). These mice were crossed with mice transgenic for Pf4-Cre-recombinase (thrombopoietic deletion) or Cd11b-Cre-recombinase (myeloid deletion). The resultant mice were compared with a Mpl–/– (thrombopoietin receptor knockout) thrombocytopenic murine model. Methods: Factor XIII-A recombination was evaluated by quantitative PCR assay of genomic DNA from liver and spleen. Factor XIII-A enzyme activity was measured in plasma and platelets with a biotin incorporation assay. quantitative PCR was performed to determine factor XIII-A mRNA levels in aortic and cardiac tissue. Factor XIII-A transcripts were assayed in human umbilical blood haemopoietic cell lineages. Findings: Selectivity of Pf4-Cre and Cd11b-Cre mediated deletion was confirmed in liver and spleen. A 40% decrease in factor XIII-A plasma activity was observed in Cd11b mice, whereas plasma activity was decreased by 85% and absent in platelets from Pf4 mice. By contrast, plasma factor XIII-A was normal in Mpl mice. Cd11b mice showed no reduction in factor XIII-A mRNA in cardiac tissue and a 54·6% reduction in aorta. A major decrease in factor XIII-A mRNA was observed in the aorta (91·6%) and heart (99·2%) of Pf4 mice, but there was no change in expression in either tissue from Mpl mice. In a human stem-cell study, factor XIII-A mRNA transcription increased as common myeloid progenitors committed to become granulocyte-macrophage progenitors and as megakaryocyte-erythroid progenitors differentiated to both megakaryocytes and erythroblasts. Interpretation: These results raise the possibility that a unique Pf4-dependent, Mpl-independent progenitor cell is the major source of the plasma pool. These findings might have implications for the management of factor XIII-A deficiency states. Funding: British Heart Foundation.